DIPG-07. Preclinical and case study results underpinning the phase II clinical trial testing the combination of ONC201 and paxalisib for the treatment of patients with diffuse midline glioma (NCT05009992). (3rd June 2022) - Dun, Matthew D; Jackson, Evangeline R; Duchatel, Ryan J; Persson, Mika L; Mannan, Abdul; Yadavilli, Sridevi; Parackal, Sarah; Game, Shaye; Chong, Wai Chin; Jayasekara, Samantha; Le Grand, Marion; Kearney, Padraic S; et al.
Abstract: Diffuse midline gliomas (DMG), including those of the brainstem (diffuse intrinsic pontine glioma - DIPG), are pediatric CNS tumors recognized as the most lethal of all children's cancers. Palliative radiotherapy is the only approved treatment, with survival just 9-11–months post-diagnosis. ONC201 shows preclinical and emerging clinical efficacy in early-stage clinical trials, extending survival of DIPG patients by ~9-11–months compared to historic controls. However, patients invariably develop resistance, with some patients completely refractory to treatment. Using a multi-omics approach, including pharmacology, proteomics, genomics, epigenetics, in vitro and in vivo modeling, across ten international laboratories, we have uncovered the inherent mechanisms of resistance to ONC201. We find ONC201 elicits antagonism of the Dopamine receptor D2 (DRD2), whilst also causing mitochondrial degradation through potent agonism of the Mitochondrial protease CLPP, that drives proteolysis of the electron transport chain (ETC) protein Succinate dehydrogenase A (SDHA) and degradation of critical mitochondrial tricarboxylic acid (TCA) cycle regulator Isocitrate dehydrogenase 3B (IDH3B). Loss mitochondrial respiration increased hypoxia and reduced α-ketoglutarate, inhibiting lysine demethylation, increasing methylation of H3K4me3 and H3K27me3, thus altering the epigenome of primary DIPG cells. Loss of SDHA caused oxidation of succinate forming superoxide driving redox regulated PI3K/AKT signaling, counteracted using the PI3K/AKT inhibitor paxalisib. The combination of ONC201 and paxalisib synergically extended survival of two aggressive DIPG PDX models (SU-SIPG-VI vehicle=73 vs. combination=100-days, p=0.0027; SF8626 vehicle=36 vs. combination=43-days, p=0.0002). Compassionate access to this combination (n=2 patients; immediately post-RT and following re-RT) resulted in reductions in tumor volume and complete resolution of disease symptoms, extending overall survival (e.g., diagnosis patient MR axial scan=1554 mm2, following eight months on the combination, current tumor volume=464 mm2 (<70%), patient remains on treatment). Our findings harness the powerful anti-DMG/DIPG pharmacokinetic/dynamic properties of ONC201 and paxalisib, a combination that is currently in clinical trials (NCT05009992).